Lógica financeira e transformações no campo de abastecimento de água e esgotamento sanitário no Brasil: uma análise a partir das trajetórias das elites empresariais - Bizzetto, Henrique Melo (Universidade Federal de São Carlos, 2025)
The field of water supply and sanitation service providers in Brazil initially emerged under state dominance, an arrangement that prevailed until the 2000s. However, the field has undergone a true transformation in its dynamics, with the implementation of corporate control models and conceptions driven by financial logic, alongside the consolidation of private companies in the sector. This study proposes that the financialization of the economy and a business management model centered on generating shareholder value are key elements. It aims to understand how this model influences the business elites involved and transforms the existing structures within the sector. The study focuses on the period from 2013 to 2023, using a case study of business elites based on company revenue, including two companies controlled by the State until 2023 (SABESP and COPASA-MG) and two private sector companies (AEGEA and BRK). Methodologically, this is qualitative research grounded in the principles of abductive analysis, seeking to confront empirical data with the theoretical approach of Fligstein (1990), particularly his concept of “conception of corporate control” and its transformations. Data collection relied on historical research, legislation, financial reports, corporate records, and executive résumés, all used to build a connected narrative with the theory that explains the identified phenomena. The most important findings reveal that state regulatory conceptions aimed at attracting private investment have encouraged arrangements between the sector’s major companies and the financial field, bringing private elites into the sanitation sector. The state-controlled companies moved toward the capital markets, and their management models quickly aligned with the “best practices” of corporate governance and shareholder value creation. The private companies, in turn, initially approached the financial field to enter the sector, but now simultaneously use public financing tools and adopt financialized control practices that fluctuate in intensity depending on their closeness to the financial field.
Financial logic and transformation in the water supply and sanitation secto in Brazil: an analysis based on the trajectories of business elites
Keywords: Concepções de controle; Financeirização; Economia pública; Serviços de abastecimento de água e esgotamento sanitário; Conceptions of control; Financialization; Public economy; Private economy; Water supply and sanitation services; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE SETORES ESPECIFICOS